Unpacking Writing Assessment Tasks for Junior High School Students: A Comprehensive Analysis - Hidayah Nor; Saadillah; Nada Afifi (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This research addresses the issue of using course books as the sole source for writing assessment tasks in junior high schools without considering students’ diverse learning needs and capabilities. The study aims to identify and describe the assessment tasks employed by teachers to evaluate the writing skills of junior high school students and investigate students’ perceptions of these tasks. A descriptive qualitative method was used, focusing on MTs Hidayatullah Bahaur in Central Kalimantan as the research setting. Two English teachers and ten students of Class VIII from MTs Hidayatullah Bahaur participated in the study. The data collection techniques included observation, interviews, and documentation. The findings reveal that the English teachers primarily used two categories of assessment tasks: imitative writing, encompassing handwriting, spelling, and punctuation tasks, and intensive writing, which involved grammatical transformation, picture cues, vocabulary assessment, ordering, short-answer, and sentence-completion tasks. Furthermore, interviews with student representatives indicated that the overall quality of the assessment tasks was satisfactory. However, students emphasized the importance of teachers actively explaining the task requirements, as understanding the tasks was crucial for successful completion. Consequently, this study highlights the significance of well-designed assessment tasks accompanied by clear explanations to ensure students’ comprehension and accurate task execution.